2019
DOI: 10.1200/jco.19.01492
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab Combined With Brentuximab Vedotin for Relapsed/Refractory Primary Mediastinal Large B-Cell Lymphoma: Efficacy and Safety From the Phase II CheckMate 436 Study

Abstract: PURPOSE Primary mediastinal B-cell lymphoma (PMBL) is a rare but aggressive non-Hodgkin lymphoma with poor outcomes in patients with relapsed/refractory (R/R) disease. PMBL is characterized by high expression of programmed death-1 ligand and variable expression of CD30. Nivolumab, an anti–programmed death-1 immune checkpoint inhibitor, and brentuximab vedotin (BV), an anti-CD30 antibody–drug conjugate, may have synergistic activity in R/R PMBL. METHODS The expansion cohort of the open-label, phase I/II CheckMa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(112 citation statements)
references
References 24 publications
5
105
0
2
Order By: Relevance
“…Furthermore, they also demonstrated that CD38 knock out tumors exhibit delayed growth when compared to CD38 + wild-type tumors in wild-type mice and that in tumor-bearing mice, combination of anti-CD38 antibody and anti-PDL-1 acts synergistically to suppress tumor growth and dissemination. These findings support the use of this combination in the clinical setting in the attempt to overcome resistance to checkpoint blockade, especially in those tumors where PD-1/PDL-1 inhibitors are especially effective, such as r/r cHL or primary mediastinal B-cell lymphoma (PMBCL) [94][95][96][97]. So far, this combination has been investigated in MM, where patient recruitment has been completed and final results are being elaborated (clinicaltrials.gov), and is currently being tested in HL/NHL (Table 1).…”
Section: Cd38 In the Era Of Immunotherapy And Cellular Therapysupporting
confidence: 53%
“…Furthermore, they also demonstrated that CD38 knock out tumors exhibit delayed growth when compared to CD38 + wild-type tumors in wild-type mice and that in tumor-bearing mice, combination of anti-CD38 antibody and anti-PDL-1 acts synergistically to suppress tumor growth and dissemination. These findings support the use of this combination in the clinical setting in the attempt to overcome resistance to checkpoint blockade, especially in those tumors where PD-1/PDL-1 inhibitors are especially effective, such as r/r cHL or primary mediastinal B-cell lymphoma (PMBCL) [94][95][96][97]. So far, this combination has been investigated in MM, where patient recruitment has been completed and final results are being elaborated (clinicaltrials.gov), and is currently being tested in HL/NHL (Table 1).…”
Section: Cd38 In the Era Of Immunotherapy And Cellular Therapysupporting
confidence: 53%
“…14 Furthermore, combination brentuximab vedotin 1 nivolumab showed even more robust activity, with an overall response rate of 73%. 15 The patient in this case study received 5 cycles of pembrolizumab, and PET/CT scans showed a complete metabolic response.…”
Section: Patient Case Study 2: Primary Mediastinal Large B-cell Lymphomamentioning
confidence: 71%
“…Therefore, the attention is now focusing on how improving the response and on overcoming the resistance to CPis. Based on a rationale that DNA damaging agents are able to promote immunogenicity of cancer cells trough increasing neo‐antigen repertoire, inducing immunogenic cell death and changing the cytokine milieu into the tumor microenvironment, with a consequence redistribution and increase expression of PDL‐1 on tumor cells, good results are being achieved combining PD1 inhibitors with chemotherapy, both in solid tumors and in lymphomas setting 20‐24 . On the other side, patients who already failed anti‐PD1 therapy, seems to benefit from a re‐treatment with conventional CHT, leading to the idea that PD1 inhibitors can re‐sensitize tumor cells to conventional treatment, previously failed 12,13 .…”
Section: Discussionmentioning
confidence: 99%